(untitled) (Research, Society and Development, 2021)
Football is the most popular sport throughout the world, the high rate of injuries among sportspeople occurs in both the amateur and professional categories, over 92% of all injuries affect the lower limbs. Hamstring injuries are much more common among athletes. The purpose of this review was to scrutinize the physical therapy interventions in rehabilitating soccer players who suffered a muscle strain in the hamstrings according to the scientific literature. It is about an integrative review that was carried out in the SciELO, LILACS, PEDro, PubMed databases, in June and August 2021. Two randomized clinical trials and one prospective study were included. This way, it is possible to view the researches which were carried out between 2014 and 2020.Each rehabilitation plan in the study has 3 treatment stages. After each rehabilitation exercise, it is applied ice to the back of the thigh for 20 minutes. Subjects/participants got into the second stage when they could walk on injured and not injured limbs with the same stride length and support time, and start painless isometric contraction of the hamstrings when the knee joint was flexed to 90°, at least Test the muscle strength of the hand 4/5. According to the studies discussed in this review, physiotherapy reveals that rehabilitation programs, including eccentric exercises, stabilization of the trunk, cryotherapy, sprint training, and mobilization, are effective in recovering soccer players who have suffered strains in the hamstrings, in reducing pain, improving function, and returning to sports, reducing the risk of recurring injuries.